"Insert" Technology in Forming Reading Comprehension Skills of Primary Class Students - Abdijamilova Mahfuza Makhmudovna (Genius Journals, 2023)
The article describes the use of "Insert" technology in the formation of reading comprehension skills of primary school students
Keywords: Reading Comprehension; Text; Interactive